2010
DOI: 10.1002/chem.200903235
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed CN Bond Formation with Heteroaromatic Tosylates

Abstract: A protocol for the palladium(0)-catalyzed amidation of heteroaromatic tosylates was successfully developed. The methodology proved to be effective for a variety of heteroaryl tosylates including the pyridine, pyrimidine, quinoline and quinoxaline ring systems. Successful carbon-nitrogen bond formation with these heteroaryl tosylates could be performed with a wide range of primary amides, oxazolidinones, lactams, anilines and indoles, including one cyclic urea. Moreover, this C-N bond forming reaction provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The first Pd-catalyzed amination of aryl tosylates was reported by Hartwig in 1998 by using Pd-DBtPF [DBtPF = 1,1'-bis(di-tert-butylphosphi-no)ferrocene] as the catalyst. [14] After this discovery, some other supporting ligandsw erer eportedt of acilitate this reaction, including 2-(dicyclohexylphosphino)-2',4',6'-triisopropylbiphenyl( XPhos), [15] 1-[2-(diphenylphosphino)ferrocenyl]ethyldicyclohexylphosphine (Josiphos)-type ligands, [16] 1,1'-bis(diphenylphosphino)ferrocene (dppf), [17] 4-[2-(di-1-adamantylphosphino)phenyl]morpholine (Mor-Dalphos), [18] 2-(diphenylphosphino)-2'-methoxy-1,1'-binaphthyl (MOP)-type phosphines, [19] a Pd/N-heterocyclic carbene precatalyst, [20] and ag raphene oxide supported PdCl 2 catalyst (Figure 1). [21] Althoughp rogress has been made,i ti ss till highly desirable to develop ag eneral catalyst system for this CÀNb ond-forming process, in particular one that can handle various types of nitrogen nucleophiles[ e.g.,p rimary/secondary aliphatic amines,c yclic/acyclica mines, (het)aryl amines,N H-heterocycle, etc.]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first Pd-catalyzed amination of aryl tosylates was reported by Hartwig in 1998 by using Pd-DBtPF [DBtPF = 1,1'-bis(di-tert-butylphosphi-no)ferrocene] as the catalyst. [14] After this discovery, some other supporting ligandsw erer eportedt of acilitate this reaction, including 2-(dicyclohexylphosphino)-2',4',6'-triisopropylbiphenyl( XPhos), [15] 1-[2-(diphenylphosphino)ferrocenyl]ethyldicyclohexylphosphine (Josiphos)-type ligands, [16] 1,1'-bis(diphenylphosphino)ferrocene (dppf), [17] 4-[2-(di-1-adamantylphosphino)phenyl]morpholine (Mor-Dalphos), [18] 2-(diphenylphosphino)-2'-methoxy-1,1'-binaphthyl (MOP)-type phosphines, [19] a Pd/N-heterocyclic carbene precatalyst, [20] and ag raphene oxide supported PdCl 2 catalyst (Figure 1). [21] Althoughp rogress has been made,i ti ss till highly desirable to develop ag eneral catalyst system for this CÀNb ond-forming process, in particular one that can handle various types of nitrogen nucleophiles[ e.g.,p rimary/secondary aliphatic amines,c yclic/acyclica mines, (het)aryl amines,N H-heterocycle, etc.]…”
Section: Introductionmentioning
confidence: 99%
“…The first Pd‐catalyzed amination of aryl tosylates was reported by Hartwig in 1998 by using Pd–DB t PF [DB t PF=1,1′‐bis(di‐ tert ‐butylphosphino)ferrocene] as the catalyst . After this discovery, some other supporting ligands were reported to facilitate this reaction, including 2‐(dicyclohexylphosphino)‐2′,4′,6′‐triisopropylbiphenyl (XPhos), 1‐[2‐(diphenylphosphino)ferrocenyl]ethyldicyclohexylphosphine (Josiphos)‐type ligands, 1,1′‐bis(diphenylphosphino)ferrocene (dppf), 4‐[2‐(di‐1‐adamantylphosphino)phenyl]morpholine (Mor‐Dalphos), 2‐(diphenylphosphino)‐2′‐methoxy‐1,1′‐binaphthyl (MOP)‐type phosphines, a Pd/N‐heterocyclic carbene precatalyst, and a graphene oxide supported PdCl 2 catalyst (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Earlier work to form pyridine based oxazolidinone was mostly done with preformed oxazolidinone derivatives. 38,39 A recent report, using non-pyridine substrates, showed that in the presence of SOCl 2 and a base, 1,2 amino alcohols can form oxazolidinones with the inversion or retention of the configuration, 24 depending on the substituents. Based on that proposed mechanism, we should obtain an inversion of the configuration during product formation and indeed, we obtained the inverted product in a major yield, although unlike the earlier report, we had no added base to our a Reaction conditions: 4-bromoanisole (0.093 g, 0.5 mmol), phenylboronic acid (0.0915 g, 0.75 mmol), base (1.5 mmol), EtOH (5 mL).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the activation/cleavage of the CO bond of tosylates in CN cross‐coupling has attracted the attention of academic research groups . Skrydstrup's group reported the Pd(dba) 2 ‐catalyzed amination reactions of heteroaromatic tosylates including pyridine, pyrimidine, quinoline and quinoxaline ring systems, with a wide range of primary amides, anilines and indoles . César and co‐workers smoothly achieved the CN cross‐coupling of aryl tosylates with amines and anilines using an N ‐heterocyclic carbene/Pd(II) precatalyst.…”
Section: Introductionmentioning
confidence: 99%